The joining of advanced high strength steels using resistance spot welding. - Christopher Carl Edward Miller (2008)
Weight reduction of the automotive body-in-white structure is increasingly necessary to improve fuel efficiency and reduce the carbon emissions and environmental impact of motor vehicles. This must be achieved without compromising the strength of the body-in-white structure. Steel manufacturers are continuing to develop advanced high strength steels (AHSS) which not only exhibit high strength and excellent energy absorbing characteristics but also retain a comparable degree of formability to low alloy grades. The specific properties of advanced high strength steels such as dual phase and TRIP are derived via the addition of specific alloying elements and careful control of thermomechanical processing routes in order to develop the required microstructures in the final product. The utilisation of such grades could yield significant reductions in the weight of body-in-white structures since they offer the automotive design engineer the opportunity to fabricate components out of thinner sheet whilst retaining or even improving on the structural strength and impact performance of components fabricated from thicker mild steel sheets. A major barrier to the widespread acceptance and implementation of AHSS by the automotive industry is the perceived complexities associated with the joining of these materials using resistance spot welding, which remains the dominant joining process in modem automobile construction. The complex alloy chemistries of these grades coupled with the extremely high cooling rates generated by the resistance welding process can give rise to weld microstructures with properties differing greatly from the parent microstructure. Of particular concern for automotive manufacturers is the potential for the formation of martensite in the weld nugget and heat affected zones, since its high hardness and low ductility are thought to result in poor weld performance. This research programme has investigated the weldability of six AHSS grades in comparison to low alloy grades typical of those currently used in the automotive industry, using a basic single pulse weld schedule. Simple modifications to welding parameters such as increasing electrode force and electrode tip diameter were investigated as well as the effects of advanced weld schedules on weld microstructures, microhardness and strength. The effect of joining selected advanced high strength steels to low carbon mild steel has also been studied.